Perbandingan Pengaturan Delik Penganiayaan menurut KUHP 1946 dan KUHP 2023 dalam Perspektif HAM - Perga Piolika; Nining Yurista Prawitasari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the comparison of the regulation of persecution offenses in the Criminal Law Code of 1946 and the Criminal Law Code of 2023 and review it from a human rights perspective. This study uses normative legal research methods with legislation, conceptual and case approaches. The results showed that the 2023 criminal code retained the substance of the regulation of the offense of persecution in the 1946 criminal code, but updated the formulation of norms, the criminal system of fines and the orientation of punishment. In the perspective of Human Rights, the arrangement has protected the right to bodily integrity, but has not optimally accommodated the protection of psychological impact and recovery of victims.